Examining Social Support and Trust Transfer Theory in Online Health Community Adoption - Saputra, Ragil; Dharmawan, Bagus Dwiky; Adhy, Satriyo; Mutiara, Dinar; Yasin, Hasbi (Jurnal Sistem Informasi Bisnis, 2025)
Online Health Communities (OHCs) have become a key source of social support for individuals with health concerns. OHC members engage in communication and information exchange, with trust among members playing a crucial role in the acceptance of these platforms. This research aims to examine the determinants affecting OHC acceptance by employing trust transfer theory, social support, and self-efficacy as core variables. The proposed model was empirically tested using data from 100 members of the Indonesian Diabetes Forum on Facebook. This quantitative study employed a 5-point Likert scale to evaluate user perceptions. The findings indicate that OHC acceptance is significantly supported by both information support and emotional support, which foster trust among community members. Trust in members subsequently leads to trust in the broader community, culminating in the sustained use of the OHC. Furthermore, emotional support positively influences self-efficacy, encouraging users to join and actively participate in OHCs. However, information support does not have a significant effect on self-efficacy. This research offers significant understanding of the relationships among social support, self-efficacy, and trust in promoting the continued use of OHCs. The research model offers a framework that can be applied in other contexts with similar technological and community-based perspectives.